Assessment of Arthrobacter viscosus as reactive medium for forming permeable reactive biobarrier applied to PAHs remediation - Ferreira, L. (2013)
Polycyclic aromatic hydrocarbons (PAHs) are significant environmental contaminants as they are present naturally as well as anthropogenically in soil, air and water. In spite of their low solubility, PAHs are spread to the environment, and they are present in surface water, industrial effluent or groundwater. Amongst all remediation technologies for treating groundwater contaminated with PAHs, the use of a permeable reactive biobarrier (PRBB) appears to be the most cost-effective, energy efficient, and environmentally sound approach. In this technology, the microorganisms are used as reactive medium to degrade or stabilize the contaminants. The main limits of this approach are that the microorganisms or consortium used for forming the PRBB should show adequate characteristics. They must be retained in the barrier-forming biofilm, and they should also have degradative ability for the target pollutants. The aim of the present work is to evaluate the viability of Arthrobacter viscosus as bioreactive medium for forming PRBB. Initially, the ability of A. viscosus to remove PAHs, benzo[a]anthracene 100 μM and phenanthrene 100 μM was evaluated operating in a batch bench-scale bioreactor. In both cases, total benzo[a]anthracene and phenanthrene removals were obtained after 7 and 3 days, respectively. Furthermore, the viability of the microorganisms was evaluated in the presence of chromium in a continuous mode. As a final point, the adhesion of A. viscosus to sepiolite forming a bioreactive material to build PRBB was demonstrated. In view of the attained results, it can be concluded that A. viscosus could be a suitable microorganism to form a bioreactive medium for PAHs remediation.